EFFECTIVENESS OF THE NEXT GENERATION SOCIAL WELFARE INFORMATION SYSTEM (SIKS-NG) PROGRAM IN HANDLING POVERTY IN SUMORAME VILLAGE - Damayanti, Yesa Apriliya; Sukmana, Hendra (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the effectiveness of the Next Generation Social Welfare Information System (SIKS-NG) program in poverty alleviation efforts at the village level, especially in Sumorame Village, Indonesia. Method: The method used is descriptive qualitative with data collection techniques through interviews, observations, and documentation. The informants involved in this study consisted of village heads, SIKS-NG operators, and village officials who were directly involved in the implementation of the program. Results: First, human resource readiness is relatively good but is still limited to verification authority and time management. Second, technological infrastructure is adequate and supports system operations. Third, system management runs procedurally but lacks coordination because village authority is limited. Fourth, data accuracy is constrained by long validation and uncertain results. Fifth, the impact of the system on organizations and communities is not optimal because it still relies on old data and limited quotas. Novelty: The novelty of this study lies in the application of effectiveness theory as a whole in the village context and the disclosure of real implementation obstacles in the field. This study provides an important contribution to policy formulation in optimizing e-government services in social welfare programs in rural areas.